Waterlogging Assessment of Chinese Ancient City Sites Considering Microtopography: A Case Study of the PuZhou Ancient City Site, China - Xinyuan Chai; Youqiang Dong; Yihao Li (Remote Sensing, 2022)
A waterlogging assessment framework based on the stormwater management model (SWMM), considering the microtopography, is proposed (taking into account the complexity of the underlying surface, which contains various micro-surface features within the Chinese ancient city site). We used the ancient city site of PuZhou as the study case and the framework is detailed in this paper. First, the land cover was classified by combining the analysis of UAVs and field surveys; subsequently, a revised sub-catchment division method considering the land cover was proposed to obtain more accurate and reliable sub-catchments; thirdly, the parameters used in SWMM were determined by analyzing the micro-surface features; finally, the inundation area was calculated based on the SWMM-GIS. To verify the advantage of our proposed framework, two comparative experiments where the land cover and the micro-surface features were not considered in the stages of the sub-catchment division and parameter estimations were carried out. The simulated inundation area derived from our proposed framework with the return periods of 10a., 50a., 100a., and 1000a. were (separately) 22,500 m2, 29,500 m2, 33,600 m2, and 44,200 m2, which are more in line with the actual situation compared with the two designed comparative experiments. The experimental results show that our proposed framework has significant meaning to the waterlogging assessment on the Chinese ancient city site.